STRATEGI PENYAMPAIAN PESAN DAKWAH PADA MEDIA SOSIAL: STUDI ANALISIS STRATEGI DAKWAH HUSEIN BASYAIBAN DI AKUN TIK TOK @KADAMSIDIK00 - Ainur Rofiq; Aviatus Sholihah (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2024)
The Da'wah message is the message that the da'i wants to convey to the mad'u which is an important element in da'wah activities. Various media can be used to carry out da'wah, such as Tik Tok. One of the platforms that is widely used by people today. One of them is Husain Basyaiban with the Tik Tok account @kadamsidik00, which discusses Islamic values ​​and da'wah messages packaged in a way that is easy to understand. This research uses qualitative research. Researchers used content analysis on the @kadamsidik00 account. These data are processed and analyzed to identify strategies for delivering da'wah messages and supporting and inhibiting factors that influence the effectiveness of the da'wah message strategies delivered. Based on the results of this research, it was found that the @kadamsidik00 account used various strategies in conveying da'wah messages on Tik Tok. One of them is the use of creative content that attracts attention, as well as the ability to follow popular trends on Tik Tok to maximize audience reach. Apart from that, interaction with followers through comments and responses is also an important part of this account's strategy. Researchers also found several significant supporting factors in the strategy of conveying da'wah messages on Tik Tok social media by the account @kadamsidik00. These factors include the ability to create creative and attention-grabbing content, adaptation to popular trends, active interaction with followers, and the popularity of accounts that can expand the reach of preaching messages. However, there are also inhibiting factors that need to be considered. Limits on the duration of content on Tik Tok, competition with other viral content, and the risk of the da'wah message being distorted can become obstacles in conveying the da'wah message effectively. Apart from that, the importance of understanding the target audience more precisely and the risk of exposure to negative content also needs to be considered.